2023
DOI: 10.3389/fnut.2022.1087505
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and lifestyle management of the aging journey: A narrative review

Abstract: With age, the physiological responses to occasional or regular stressors from a broad range of functions tend to change and adjust at a different pace and restoring these functions in the normal healthy range becomes increasingly challenging. Even if this natural decline is somehow unavoidable, opportunities exist to slow down and attenuate the impact of advancing age on major physiological processes which, when weakened, constitute the hallmarks of aging. This narrative review revisits the current knowledge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 228 publications
0
6
0
Order By: Relevance
“…Together, our findings suggested that the capacity of neuronal metabolism was quite limited, heavily depended on astrocytic metabolism. Considering age‐related reduction in intestinal, 54 malnutrition of astrocytes might potentially account for some late‐onset PD like symptoms in clinical.…”
Section: Discussionmentioning
confidence: 99%
“…Together, our findings suggested that the capacity of neuronal metabolism was quite limited, heavily depended on astrocytic metabolism. Considering age‐related reduction in intestinal, 54 malnutrition of astrocytes might potentially account for some late‐onset PD like symptoms in clinical.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the trials differed in age distributions; the mean age in PHS2/COSMOS was 64/72 years, while the mean age of females/males in SU.VI.MAX was 47/51 years [ 5 7 ]. Aging is associated with insufficiency of metabolism of specific micronutrients [ 16 , 17 ]; this could be due to inadequate intake or deficient absorption of those micronutrients (i.e., vitamin B12, vitamin D, calcium …) [ 17 ]. Because the sex-specific cancer preventive effect did not change with age, since it was apparent in SU.VI.MAX (mean age of males was 51 years) as well as in on average 13 years older PHS2 participants and in on average ~ 20 years older COSMOS participants (the non-significant effect in COSMOS was likely due to the short time frame of COSMOS), we speculate that the metabolism of micronutrient(s) being responsible for the observed positive signal of our meta-analysis is not influenced by age.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, adequate intake of these nutrients supports optimal cellular function and may help delay or mitigate senescence [103]. The Mediterranean diet (MedDiet) is a plant-based eating pattern that was traditionally followed in countries, such as Greece, Spain, and Italy before the global spread of the modern food system.…”
Section: The Importance Of Lifestyle: Diet Nutrition and Physical Act...mentioning
confidence: 99%